The institute of persuasive communication in the management of socio-political and economic processes of society - Tamara V. Naumenko, Ilya V. Ilyin, (Opción, 2020)
The article analyzes various types and forms of persuasive communication, affecting the management of the political and socio-economic space of modern society by influencing the consumer behavior. The main types of persuasive communication, such as public relations and advertising, as well as their methods and means of achieving their goals, such as images, performance, flash mob, branding, are considered. Besides, the problem of consumerism of society is considered, manifested in the transformation of society’s consciousness, deideologization and the formation of consumer ideology and culture, which leads to devastating consequences for the political space of modern society